Students’ Attitude to Social Media in Distance Education: Implications for Quality Instructional Delivery in Physics - Funke Susan Apata (Universitas Syiah Kuala, 2021)
This study examined students’ attitudes to social media (SM) at the National Open University of Nigeria (NOUN) and its implications for quality instructional delivery in physics. The stratified random sampling technique selects the sample size of 640 students that form the representatives from each faculty viz; Arts, Education, Management Sciences, and Science Technology. The number of social media used for the study is twenty-nine in number. The eclectic integration of instruments developed by researchers made the instruments whose reliability and validity were determined. Two research questions and two hypotheses guided the study. Research questions were analysed using descriptive statistics, while ANOVA and t-test analysis was for the hypotheses. Results showed that the attitude of students towards SM was above average (71.66 %). The mean attitudes of female students (67.81) towards SM were higher than their male (62.31) counterparts. The most known social media is Facebook (90%). Findings on DL students’ attitudes in different fields of the study showed no significant difference (p0.05). Students from the faculties of Education and Science Technology scored the highest mean value in attitude to SM. However, the faculty of Management Sciences recorded the lowest attitude to SM. The recommendation was that e-learning oriented programmes that promote attitudes to social media should be in the curriculum. It concluded that positive attitudes recorded by students to social media in Education and Science could leverage transformation in the instructional delivery of physics. Also, a higher mean value for the female students portends better performance for female students in physics. It recommends social medial driven activities to the school curriculum for enhancing instructional physics delivery in distance education.